Seven highly effective police leaders: 1895-modern times - Kooi, Brandon R. (Routledge, Taylor & Francis Group, 2022)
"This book provides a valuable addition to the policing literature by detailing the backgrounds and histories of seven important police leaders: Teddy Roosevelt, August Vollmer, O.W. Wilson, Penny Harrington, Bill Bratton, Chuck Ramsey, and Chris Magnus. Seven Highly Effective Police Leaders teaches important history, highlighting the impact on the evolution of American policing by academia and social science. Each historical biography demonstrates the importance of each leader's decision-making and how it continues to shape the future of U.S. law enforcement. Readers are informed about each police leader's background and how their leadership was shaped by the political and historical environments in which they led. The book is useful for educational courses in policing, American history, leadership, and strategic planning. Additionally, the general public will find this book insightful regarding contemporary mass social justice protests linked to the unique history of the United States"--